InCIEC 2014 2015
DOI: 10.1007/978-981-287-290-6_92
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Nitrate by Eichhornia crassipes sp. in Landfill Leachate

Abstract: − . This study shows that concentration of NO 3 − was higher in young landfill (27 mg/L) than that in old landfill (9 mg/L) at neutral pH. Finding of these results indicate that Eichhornia crassipes sp. has the ability to remove NO 3 − at different concentrations in three days. Approximately 69 and 64 % of NO 3 − that present in leachate from young landfill was removed in sample without dilution and 50 % dilution, respectively. While approximately 28 and 33.6 % of NO 3 − present in leachate collected from old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
5
1
Order By: Relevance
“…From this finding, it was found that the pH value of 7.84 was still within the permissible range of 6.0-9.0. In addition, the NO 2 and NO 3 value were lacking sources for comparison purposes except for the study made by [24] for the NO 3 which was lower than the NO 3 value obtained in this study. As for the BOD, the value exceeded the standard limit of 20 mg/L.…”
Section: Characterization Of Selected Parameters In the Leachate From...contrasting
confidence: 68%
See 1 more Smart Citation
“…From this finding, it was found that the pH value of 7.84 was still within the permissible range of 6.0-9.0. In addition, the NO 2 and NO 3 value were lacking sources for comparison purposes except for the study made by [24] for the NO 3 which was lower than the NO 3 value obtained in this study. As for the BOD, the value exceeded the standard limit of 20 mg/L.…”
Section: Characterization Of Selected Parameters In the Leachate From...contrasting
confidence: 68%
“…Many studies believe that the persistent industrial production growth and trade around the world have been contributing to the increase in municipal and industrial waste production [23]. It is predicted that in the year of 2025, the production of waste globally will reach almost double to 2.2 billion tons even though all cities around the world are trying really hard to reach their waste reduction targets [23,24]. The high pH of the leachate may be caused by 82.7 mg/L of NH 3 -N which was beyond the standard limit of 5 mg/L that allowed by MEQA.…”
Section: Discussionmentioning
confidence: 99%
“…Aquatic plants have the ability to withstand the high pollution load of the landfill leachate without showing any sign of a significant cutback in biomass and growth rate [297]. Eichhornia crassipes in a floating system has shown the tremendous capacity of removing diverse HMs such as Cu, Ni, Pb, Cd and Cr from the landfill leachate, thus reducing the pollution density of the landfill leachate [298].…”
Section: Phytoremediation Of Landfill Leachatementioning
confidence: 99%
“…High nitrate levels in leachate can affect both surface water and groundwater quality. This is an issue that has attracted the attention of researchers globally (Jaya & Amir 2015;Bialowiec et al, 2012;Matthews et al, 2009;and Mangimbulude et al, 2007). Some impacts associated with nitrate contamination include: methemoglobinemia, or 'blue baby syndrome', which occurs in young children who consume excessive volumes of water contaminated with nitrates (Ribbe et al, 2008;Gupta, 2001;Gelbrerg et al, 1999;Comly, 1945); stomach cancer; and the eutrophication of water bodies, which produced toxins that reduce the level of available oxygen and impacts biodiversity in aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%